Geotecnologia em perícias ambientais e na análise da qualidade da água: estudos nos reservatórios de abastecimento público da Região Metropolitana de Belo Horizonte/MG - Marcos de Paulo Ramos (2020)
This research addresses the analysis of the efficient use of technologies on behalf of improving the analytical capabilities of the environmental legal experts, as well as a temporal evaluation of the impacts of different land uses to the water quality. The testbed of the investigation was the water supply reservoirs in the Metropolitan Region of Belo Horizonte/MG. The geotechnologies investigated were the use of orbital images from Remote Sensing and the use of spatial analysis by metrics of Landscape Ecology. At first, the dissertation brings a methodological approach was based on a sequence of exploratory analyzes of different solutions of geotechnologies applied from environmental experts. The easiness of use of geographic and multitemporal data availability, positional accuracy, and quality of data were the criteria evaluated. The pros and cons of each solution were reported regarding the identification of environmental damage in a simple, direct and persuasive manner. The results are promising and enable to orient the creation of a protocol towards the recommendation for environmental inspection and expertise. Then, in the following chapter, the research put together advanced geoprocessing techniques based on landscape analysis and transition maps to investigate the changes in land cover and land use in the environmentally sensitive region of the study and their potential impact to the variation of the Water Quality Index at different times. Findings indicate a correlation between the pattern of soil cover and water quality. Such indicators are vitally important for understanding the history and trends of environmental impacts, and the reflection of these changes in water quality. The landscape metrics allowed to analyze specific characteristics of the land cover types, such as fragmentation, proximity-isolation, and parameters derived from the spatial geometry of these classes like the area and perimeter of contact with adjacent classes. The multitemporal analysis allowed to know the dynamics of the changes and the qualification of the transitions between classes. In short, this research made it possible to obtain significant results regarding the advantages and challenges of using geotechnologies in the management of water resources as well as regarding the development of protocols and recommendations for the use of geographic data and methods of analysis to improve the environmental expertise. It is important to highlight only free software and publicly available geographic data were used in this research. This investigation was the pioneer in the context of the Post-Graduate Program in Analysis and Modeling of Environmental Systems. The theme focuses on legal environmental preservation based on the Federal Constitution that, in addition to ensuring everyone the right to an ecologically balanced environment, imposes on the public authority and on the society a duty to defend it and preserve it for present and future generations.